Spirituality Correlates with The Self- Confidence of Teenagers as Bullying Victim - Radha Idfit Istiqomah; Sri Nur Hartiningsih; Eka Oktavianto (Talenta Publisher, 2022)
Teenagers still encounter bullying, which affects their self-confidence lacking confidence. It is presumed that an internal factor, spirituality, coincides with the self- confidence of bullied teenagers. This research aims to analyze the relationship between spirituality and bullied teenagers' self-confidence. This is descriptive research using a cross- sectional design. The population is 47 teenagers who are bullied at SMP Islam Al-Irsyad Tawangmangu. Total sampling was used as the sample acquiring technique. The research use questionnaire of the Daily Spiritual Experience Scale and self-confidence. Kendall's Tau was used as a correlational test with a confidence level of 95% (Î± value = 0,05). The research shows that 31 respondents (66%) have a high spirituality and 26 respondents (53.3%) have an average level of self-confidence. Bullied teenagers have a high spiritualty and tend to have an average level of self-confidence, with 26 respondents (55.3%). Statistical test shows Kendall's Tau correlation coefficient (r-value) is 0.373 and p-value = 0.006 (p-value < 0.05). An R-value 0.373 means that the relationship between spirituality and anxiety of bullied teenagers is feeble. There is a correlation between spirituality and the self-confidence of the bullied teenager. The researcher suggested that parents and schools should provide more extracurricular activities to improve teenagers' self-confidence.